2014
DOI: 10.1149/2.0311412jes
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Design of SOFC Infiltrated Electrodes with Optimized Active TPB Density via Mechanistic Modeling

Abstract: A mechanistic model for the prediction of total and active three phase boundary density (TPB), in combination with effective conductivity, of infiltrated solid oxide fuel cell (SOFC) electrodes is presented. Varied porosities, scaffold:infiltrate size ratios, and pore:infiltrate size ratios were considered, each as a function of infiltrate loading. The results are presented in dimensionless form to allow for the calculation of any infiltrate particle size. The model output compares favorably to the available e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…A mechanistic model to predict the active TPB density, in combination with effective conductivity of infiltrated SOFC electrodes is presented by Reszka et al. . Recently Kishimoto et al.…”
Section: Introductionmentioning
confidence: 99%
“…A mechanistic model to predict the active TPB density, in combination with effective conductivity of infiltrated SOFC electrodes is presented by Reszka et al. . Recently Kishimoto et al.…”
Section: Introductionmentioning
confidence: 99%
“…In that study, they present a methodology to relate an experimentally observed degradation in the effective electronic conductivity of infiltrated electrodes to a reduction in active TPB length as a function of time. A mechanistic model to predict the active TPB density, in combination with effective conductivity of infiltrated SOFC electrodes, is presented by Reszka et al Their study showed that the scaffold/infiltrate size ratio has the greatest impact on the TPB density, followed by the porosity and pore/infiltrate size ratio. Their model provided an insight over the rational design of infiltrated electrodes and conforms well to experiment.…”
Section: Introductionmentioning
confidence: 99%
“…In doing so, performance degradation rates and cost would both decrease substantially. A key factor in improving low‐temperature SOFC performance is to increase the density of electrochemically active sites in the porous ceramic electrode composites …”
Section: Introductionmentioning
confidence: 99%
“…A key factor in improving low-temperature SOFC performance is to increase the density of electrochemically active sites in the porous ceramic electrode composites. [4][5][6][7] One of the most effective ways to increase the density of active sites is to sinter porous ceramic scaffolds, typically an oxygen anion conductor, and coat their surface with electrocatalytic and electronically conducting particles. [8][9][10][11][12][13][14][15][16] This affords unprecedented control over particle morphology because the coated particles are processed at temperatures hundreds of degrees lower than the scaffold sintering temperature.…”
Section: Introductionmentioning
confidence: 99%